Social capital and the mental health of children in rural China with different experiences of parental migration. (May 2015) - Wu, Qiaobing; Lu, Deping; Kang, Mi
Abstract: Children migrating to urban cities with their parents and children left behind in rural counties by their migrant parents are two vulnerable populations resulting from the rural–urban migration in mainland China. Some of these children even have mixed experiences of being left-behind and being migrants at different times. This study aimed to investigate how the various experiences of being left-behind, migrant, or both, might influence the mental health of children in the context of rural China. Moreover, it investigated how these effects might be mediated by the stock of social capital in their family and neighborhood. Data used in this study came from a questionnaire survey with a school-based multi-stage random sample of 701 children (aged 8–17 years) living in the rural counties of Guizhou province in 2013. The structural equation modeling results suggested that, compared to those rural children who lived with both parents and have never experienced migration or being left-behind, children who are currently left-behind, either with or without previous experience of being a migrant, appeared to exhibit higher levels of depression. However, children who had previously been left-behind, but lived with both parents at the time of study, tended to experience fewer depressive symptoms. Parental migration also influenced children's mental health through the mediating effects of family and community social capital. These research findings imply developing intervention and prevention programs tailored to different groups of children in rural China with a focus on fostering the growth of social capital using various strategies. Highlights: Distinguishes among children with various left-behind/migrant statuses in rural China. Identifies the unique effect of each migration status on the child's mental health. Reveals the role of status change in determining the mental health of children. Reveals the role of social capital as a mediator between migration status and mental health. Provides recommendations for tailored social services promoting child mental health.